Immunonutritional Biomarkers in Primary Sjögren’s Syndrome Disease Activity: CALLY Index and HALP Score - Özdoğan Bircan, Ayşegül; Zengin Acemoğlu, Şerife Şeyda; Türk, İpek; Elbek Özer, Hüseyin Turgut (Archives of Rheumatology, 2025)
Background/Aims: Primary Sjögren’s syndrome (pSS) is an autoimmune disease that can affect several systems. The purpose of this study was to examine the connection between primary Sjögren’s disease activity and the CRP-albumin-lymphocyte index (CALLY) and the HALP (hemoglobin, albumin, lymphocyte, and platelet) score, 2 novel immunonutritional indicators that have not yet been applied to rheumatological disease activation. Materials and Methods: This cross-sectional study included 89 patients with pSS and 113 age- and sex-matched individuals. The relationship between haematological, inflammatory, immunonutritional biomarkers, and disease activation was investigated, as were the differences between the groups. Results: Eighty-nine patients (96.6% female, mean age 53.4 ± 15.0 years) and 113 control subjects (97.3% female, mean age 50.8 ± 14.9 years) were included in the study. The levels of C-reactive protein (CRP), erythrocyte sedimentation rate, red cell distribution width, neutrophil lymphocyte ratio, monocyte lymphocyte ratio, platelet lymphocyte ratio, and C-reactive protein albumin ratio were significantly higher in the group of patients with pSS compared to the control group (all; P < .001). Systemic immuneinflammation index and systemic inflammatory response index were significantly elevated in the patient cohort compared to the control group (P = .002 and P = .048, respectively). The CALLY index and HALP score were negatively correlated with EULAR Sjögren’s syndrome disease activity index (P < .001 for both). Conclusion: The CALLY index and HALP score represent a novel approach to assessing disease activity and prognosis in a number of conditions, including stroke, myocardial infarction, osteoarthritis, pulmonary thromboembolism, asthma, chronic obstructive pulmonary disease, and many types of cancer. They may also be useful as a guide to disease activity and monitoring in pSS.